Pengaruh Akuntabilitas , Transparansi Anggaran, dan Partisipasi Masyarakat Terhadap Efektivitas Pengelolaan Keuangan Desa: Studi pada Desa-Desa Di Kecamatan Tilango, Kabupaten Gorontalo - Ravika Apriliany Bibitan; Hartati Tuli; Lukman Pakaya (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the influence of accountability, budget transparency, and community participation on the effectiveness of village financial management in the villages of Tilango District, Gorontalo Regency. The background of this research is based on the importance of implementing the principles of good governance in village financial management to ensure effective, efficient, and well-targeted development. Although village budgets continue to increase, the effectiveness of their management is largely determined by the extent to which village governments are able to apply accountability, ensure information transparency, and involve the community in the financial management process. This study employs a quantitative method with a survey approach. Data were collected through the distribution of questionnaires to village officials and members of the Village Consultative Body (BPD) in eight villages within Tilango District. The research instrument was tested using validity and reliability tests, and the data were analyzed using multiple linear regression through SPSS. Classical assumption tests were also conducted prior to the regression analysis. The results of the study indicate that: (1) accountability has a positive and significant effect on the effectiveness of village financial management; (2) budget transparency has a positive and significant effect on the effectiveness of village financial management; (3) community participation has a positive and significant effect on the effectiveness of village financial management; and (4) simultaneously, these three variables have a positive and significant effect on the effectiveness of village financial management in Tilango District. These findings affirm that the implementation of accountable, transparent, and participatory village governance is a key factor in achieving effective village financial management.